Laparoscopic retroperitoneal para‐aortic lymph node biopsy in advanced cervical cancer with pelvic lymph node metastases: A single‐center prospective study. Issue 11 (18th August 2021) - Yoshida, Kenta; Kondo, Eiji; Matsumoto, Tsuyoshi; Maki, Shintaro; Kaneda, Michiko; Nii, Masafumi; Hirata, Toru; Ikeda, Tomoaki
Abstract: Aim: Extended‐field concurrent chemoradiation therapy (Ex‐CCRT) has been widely used for para‐aortic lymph node (PAN) metastases confirmed by radiographic assessment without surgical exploration. The objective of this prospective study was to evaluate the clinical value of laparoscopic retroperitoneal PAN biopsy in locally advanced cervical cancer (LACC) with pelvic lymph node (PLN) metastases. Methods: From May 2017 to March 2020, stage IIB–IIIB cervical cancer patients who were diagnosed with PLN metastasis using positron emission tomography‐computed tomography (PET‐CT) with maximum standardized uptake value (SUVmax) ≥2.0 underwent laparoscopic retroperitoneal PAN biopsy. The radiation fields were extended to PAN areas with pathological metastases. Results: Fourteen patients were diagnosed with cervical squamous cell carcinoma of the International Federation of Gynecology and Obstetrics (FIGO) stage IIB ( n  = 7) and IIIB ( n  = 7). The median operating time was 138 min (range, 104–184 min). The median number of harvested PANs was 19 (range, 6–36). Three patients were positive for PAN metastasis on histological analysis. In this study, the sensitivity and specificity of PET‐CT were 66.7% and 90.9%, respectively. Conclusion: Our study is characterized by the use of more appropriate eligibility criteria for LACC with PLN metastases. Our results revealed that laparoscopic retroperitoneal PAN biopsy may be a useful approach to determine the radiation field for PANs during standard radiotherapy planning.